Oversecretion of CCL3 by Irradiation-Induced Senescent Osteocytes Mediates Bone Homeostasis Imbalance - Fanyu Zhao; Haiqing Han; Jing Wang; Jianping Wang; Jianglong Zhai; Guoying Zhu (Cells)
Various stressors such as ionizing radiation (IR), chemotherapeutic agents, oxidative stress, and inflammatory responses can trigger the stress-induced premature senescence (SIPS) of cells in the bone microenvironment, including osteocytes. However, little is known about the mechanisms underlying the senescent cellular regulation of the differentiation potential and bone homeostasis. Here, we report a secretory change in senescent osteocytes activated by IR, its subsequent impact on osteogenic and osteoclastic differentiation, and the inflammatory cascade response. It was observed that osteocytes exhibited altered biological function, persistent and incomplete DNA damage repair, and characteristic senescence phenotypes after exposure to IR in vitro. Meanwhile, a concomitant increase in the CC chemokine ligand 3 (CCL3), a key component of the senescence-associated secretory phenotype (SASP), was observed in the IR-induced senescent osteocytes, which could further downregulate the osteogenic differentiation and enhance the osteoclastic differentiation in cell supernatant co-culture experiments. Notably, the enhancement of the PI3K/Akt/NF-κB signaling pathway in IR-induced senescent osteocytes appears to be an essential driver of the imbalance between the osteogenic and osteoclastic differentiation potentials. Taken together, these data suggest a novel role of CCL3 in IR-induced bone homeostatic imbalance through SASP cascade secretion, mediated by the PI3K/Akt/NF-κB signaling pathway.